Coastal Area Resources as a Pillar of Sustainable Development: Reorienting Education for Biodiversity Literacy - Adinugraha, Fajar; Sangur, Kristin; Rumahlatu, Dominggus; Zubaidah, Siti (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2025)
Coastal areas have high biodiversity, which is essential in supporting sustainable development. However, low biodiversity literacy among coastal communities challenges conservation efforts and sustainable resource utilization. Reorienting interdisciplinary-based education is a necessary strategy to improve people's understanding of coastal ecosystems, including coral reefs, mangrove forests, and seagrass beds. Therefore, this paper aims to analyze the potential of coastal resources as a pillar of sustainable development, identify interdisciplinary approaches that can support biodiversity literacy, and design interdisciplinary strategies in reorienting education. Various scientific fields, such as Marine Science, Agricultural Science, Education Science, Social and Political Science, Legal Science, and Education Management science, can contribute to building a holistic and community-based educational approach. Knowledge in the form of local wisdom can support coastal area management. For example, the Sasi tradition in Maluku is vital in preserving marine biodiversity by regulating the sustainable use of natural resources according to the ecosystem cycle. Through synergies between academia, government, and communities, adaptive education programs can be implemented to equip communities with sustainable marine resource management skills. This approach is in line with the Sustainable Development Goals (SDGs), particularly goals 14 (Marine Ecosystems), 4 (Quality Education) and 13 (Addressing Climate Change). With proper policy support, education in coastal areas is expected to create an environmentally aware generation, adapt to global challenges, and actively preserve marine ecosystems for sustainable prosperity.